2008
DOI: 10.1016/j.jacc.2007.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Atrial Fibrillation Is Associated With Reduced Risk of Torsades de Pointes in Patients With Drug-Induced Long QT Syndrome

Abstract: This study strongly suggests that despite ongoing rate irregularity, AF reduces the likelihood of developing TdP after the administration of drugs that prolong cardiac repolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
2
29
0
1
Order By: Relevance
“…The serum [K + ] in rabbits after 4 weeks on a low-K + diet decreased by approximately 50% compared with the control rabbits (low K + , 2.4 mM; control, 4.69 mM), and the hypokalemic rabbits displayed a prolonged QT interval (low K + , 0.36 seconds; control, 0.27 seconds). Hypokalemia is defined as a serum K + level less than 3.5 mM (30), and the condition has been associated with the occurrence of cardiac arrhythmic events such as Torsades de pointes (30)(31)(32). In hypokalemic patients, serum [K + ] of 2.1 and 2.8 mM were reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…The serum [K + ] in rabbits after 4 weeks on a low-K + diet decreased by approximately 50% compared with the control rabbits (low K + , 2.4 mM; control, 4.69 mM), and the hypokalemic rabbits displayed a prolonged QT interval (low K + , 0.36 seconds; control, 0.27 seconds). Hypokalemia is defined as a serum K + level less than 3.5 mM (30), and the condition has been associated with the occurrence of cardiac arrhythmic events such as Torsades de pointes (30)(31)(32). In hypokalemic patients, serum [K + ] of 2.1 and 2.8 mM were reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…9 In a recently published case-control study, Darbar and colleagues compared patients with drug-associated QT prolongation only with individuals with QT prolongation and TdP. 29 The comparison demonstrated that while on drug both groups of patients showed increased QTend-QTpeak intervals the increase in the latter group was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…the mean QTc intervals were shorter during AF than in sinus rhythm (considering the limitations of Bazett's QTc estimation for irregular rhythms 18 ), although it is important to note that heart rate was substantially higher during AF than during sinus rhythm (Table 1). A good adaptation of the QTc interval to increased heart rates has been described as a characteristic feature of LQT-3 subtypes.…”
Section: Family Screeningmentioning
confidence: 99%